Iridoids and bis-iridoids from Patrinia scabiosaefolia. Issue 40 (10th May 2017) - Liu, Zhen-Hua; Hou, Bo; Yang, Liu; Ma, Rui-Jing; Li, Jin-Yu; Hu, Jiang-Miao; Zhou, Jun
Abstract : Ten new iridoids, patriscabioins A–J (1–10 ), and three unique bis-iridoids, patriscabiobisins A–C (11–13 ), together with seven known analogues, have been identified from whole plants of Patrinia scabiosaefolia . Abstract : Ten new iridoids, patriscabioins A–J (1–10 ), and three unique bis-iridoids, patriscabiobisins A–C (11–13 ), together with seven known analogues, have been identified from whole plants of Patrinia scabiosaefolia . Compounds1 to8 are a series of 5, 6-dihydrovaltrate hydrins with unique substituent groups in the Valerianaceae family such as isovaleryl and 3-methylcrotonyl. Furthermore, compounds11 and12 are the first reported bis-iridoids with two units connected by a 1, 3-dioxane group, whereas compound13 is linked by an ether bond between two units. The structures of all the compounds were established on the basis of extensive spectroscopic analysis as well as experimental and calculated ECD spectra. Compounds1 and3 showed moderate inhibitory activities on AChE with IC50 values of 37.6 and 10.5 µM, respectively. Moreover, compounds1, 3, and5 also showed moderate cytotoxic activity against HL-60, with IC50 values ranging from 1.2 to 27.6 µM.